Gallium Concentration Optimisation of Gallium Doped Zinc Oxide for Improvement of Optical Properties - Spustaka, Agnese; Senko, M.; Millers, Donats; Bite, Ivita; Smits, Krisjanis; Vitola, Virginija (De Gruyter, 2021)
The near-band luminescence of doped ZnO is promising for advanced scintillators; however, the dopant type and concentration effects require a detailed study. Undoped and Ga-doped ZnO nanopowders were prepared by a microwave-assisted solvothermal method and the gallium concentration effect on luminescence properties was studied. The near-band luminescence peak position dependence on gallium concentration was observed. Near-band luminescence intensity versus defect luminescence intensity ratio was explored for different gallium concentrations and the optimal value was determined. Samples were prepared with dopant concentrations between 0.2 and 1.5 at%, XRD analysis confirmed that samples contained only zinc oxide hexagonal wurtzite phase. The results of the research showed that ZnO:Ga containing 0.9 at.% gallium was promising for scintillators.---//---This work is licensed under a CC BY 4.0 license.
The research has been supported by project ERA.NET RUS_ST2017-05 (Latvia) and No. 18-52-76002 (Russia). The Institute of Solid State Physics, University of Latvia as the Centre of Excellence has received funding from the European Union’s Hori-zon 2020 Framework Programme H2020-WIDESPREAD-01-2016-2017-Teaming-Phase2 under grant agreement No. 739508, project CAMART².
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics; Luminescence; microwave-assisted solvothermal synthesis; optimised concentration; scintillator; ZnO:Ga